2021
DOI: 10.1039/d1cp03439a
|View full text |Cite
|
Sign up to set email alerts
|

Can we enhance diradical character using interaction with stoichiometric surfaces of ionic oxides? A theoretical investigation using chemical indices

Abstract: Chemical indices, especially diradical character, are utilised to examine the functions and reactivity of stable radical species. In the present study, we formulated an approximation to estimate chemical indices using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 36 publications
2
31
1
Order By: Relevance
“…Stabilised diradical states in stable organic radicals, transition metal complexes, and metal clusters are the origin of their unique optical, electrochemical, and catalytic properties [1][2][3][4][5][6]. Diradical character (y), which is defined as the contribution of two-electron excited states, is a key factor in studying singlet diradical states [1,[7][8][9][10][11]. For example, it has been confirmed that the y value is correlated with hyperpolarizability in third-order nonlinear Regular Paper e-J.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Stabilised diradical states in stable organic radicals, transition metal complexes, and metal clusters are the origin of their unique optical, electrochemical, and catalytic properties [1][2][3][4][5][6]. Diradical character (y), which is defined as the contribution of two-electron excited states, is a key factor in studying singlet diradical states [1,[7][8][9][10][11]. For example, it has been confirmed that the y value is correlated with hyperpolarizability in third-order nonlinear Regular Paper e-J.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnol. 20, 59-67 (2022) | DOI: 10.1380/ejssnt.2022-011 optics [1,10,11], and it can be used for the analysis of covalent bonds because the y value is also correlated with the effective bond order [1,[7][8][9]. Ten years ago, it was proved that the y value can be experimentally estimated, and the equation for the experimental estimation of the y value is as follows:…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations